The right of information privacy between the challenges of technology and the reality of legal protection - Mustafa, Aisha Ben Qara (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed to identify the international, regional and even national efforts to protect the rights and privacy of the individual from the impact of informatics, and the extent to which it succeeded in achieving this. To achieve this, the researcher used the analytical method by explaining the new technical challenges to personal data and various legal mechanisms to protect this right. The research was based on an introduction, two papers and a conclusion. The first topic was entitled "What is the privacy of informatics and the dangers it faces in the digital age", while the second topic is devoted to international and regional efforts to protect information privacy. The results of the study showed that most of the legislations, especially the Arab ones, are not able to deal with violations of personal data, and concluded that new legal rules must be enacted to protect information privacy, based on established international principles in the field of informatics.